YOUTH PERCEPTION ON NATIONAL SECURITY IN MALAYSIA - Suhaimi, Safiah; Roslam, Aini Fatihah (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This article examines Malaysian youth’s perception of national security within the context of contemporary threats and societal transformation. Youth represent a large and influential demographic in Malaysia, yet their role in security discourse remains underexplored. Using a qualitative approach supported by selected case studies, the study analyses the level of awareness, trust, and engagement of youth in national security matters. Findings indicate that while Malaysian youth demonstrate high concern regarding issues such as cyber threats, social cohesion, and political instability, their understanding of the national security structure and their roles within it remains limited. The study also finds that formal government programmes like the National Service Training Programme (PLKN) and the Police Undergraduate Voluntary Corps (SUKSIS) yield mixed outcomes in fostering security awareness. Meanwhile, informal initiatives—such as youth-led cyber defence movements—reflect the potential of youth as key stakeholders in non-traditional security domains. The article proposes several policy recommendations including the institutionalisation of security literacy, expanded youth participation in strategic communication, and the development of inclusive security policies that reflect the voice and needs of Malaysia’s younger generation.